AIB1 cooperates with ERα to promote epithelial mesenchymal transition in breast cancer through SNAI1 activation. - Miao Wang (Public Library of Science (PLoS), 2013)
Epithelial Mesenchymal Transition (EMT) plays a major role in cancer metastasis. Several genes have been shown to play a role in EMT, and one of these is Amplified-in-breast cancer 1 (AIB1), which has oncogenic function and is known to be amplified in breast cancer. However, the role of AIB1 in EMT remains largely undefined at the molecular level. In this study, the effect of AIB1 overexpression on the EMT of the breast cancer cell line T47D was investigated. Overexpression of AIB1 disrupted the epithelial morphology of the cells. At the same time, the cells displayed a strong metastasis and reduced level of the epithelial marker E-cadherin. In contrast, knockdown of AIB1 in T47D cells increased cell-cell adhesion and produced weak metastasis, as well as a higher level of E-cadherin expression. We proposed that the regulation of EMT by AIB1 occurred through the action of the transcription factor SNAI1, and demonstrated that such interaction required the participation of ERα and the presence of ERα-binding site on SNAI1 promoter. The expression level of E-cadherin and the extent of cell migration and invasion in SNAI1-knocked down T47D cells that overexpressed AIB1 were similar to those of T47D cells that did not overexpress AIB1 and had no SNAI1 knockdown. Taken together, these results suggested that AIB1 exerted its effect on EMT through its interaction with ERα, which could directly bind to the ERα-binding site on the SNAI1 promoter, allowing the AIB1-ERα complex to promote the transcription of SNAI1 and eventually led to repression of E-cadherin expression, consistent with the loss of E-cadherin being a hallmark of EMT.